Enhancing accounting education through the Kurikulum Merdeka: Opportunities and challenges - Annisa Rizki Pebriani; Aghnia Ilmi Diniyati; Mazaya Faudya Nur Aufa; Ardhan Mardiant (Universitas Pendidikan Indonesia, 2025)
Education plays an important role in developing quality human resources. In Indonesia, the Kurikulum Merdeka is designed to respond to global challenges and local needs by providing flexibility in learning. This is relevant to the scope of Vocational High Schools (SMK), especially in accounting education, which faces challenges from outdated materials and monotonous teaching methods. This Merdeka curriculum applies project-based learning and technology integration to increase relevance and practicality. The success of implementing the curriculum depends on teacher readiness and resource availability. This study aims to examine the implementation of the Kurikulum Merdeka in SMK with a focus on transforming accounting education to match industry demands. A qualitative approach through in-depth interviews was used as the main method. The results show that the Merdeka Kurikulum provides greater flexibility for teachers to design contextual and applicable learning, such as financial statement simulations. Despite the positive impact, barriers such as limited teaching materials and teacher readiness are still significant. These obstacles need to be overcome by improving the transformation of accounting education in SMK to be more in line with the needs of the world of work. Abstrak Pendidikan berperan penting dalam mengembangkan sumber daya manusia berkualitas. Di Indonesia, Kurikulum Merdeka dirancang untuk menjawab tantangan global dan kebutuhan lokal dengan memberikan fleksibilitas dalam pembelajaran. Hal tersebut relevan pada ruang lingkup Sekolah Menengah Kejuruan (SMK) khususnya pada pendidikan akuntansi yang menghadapi tantangan berupa materi usang dan metode pengajaran monoton. Kurikulum Merdeka ini menerapkan pembelajaran berbasis proyek (PjBL) dan integrasi teknologi untuk meningkatkan relevansi serta kepraktisan. Keberhasilan penerapan kurikulum tersebut bergantung pada kesiapan guru dan ketersediaan sumber daya. Penelitian ini bertujuan untuk mengkaji implementasi Kurikulum Merdeka di SMK dengan fokus pada transformasi pendidikan akuntansi supaya sesuai dengan tuntutan industri. Pendekatan kualitatif melalui wawancara mendalam digunakan sebagai metode utama. Hasil penelitian menunjukkan bahwa Kurikulum Merdeka memberikan fleksibilitas lebih besar bagi guru untuk merancang pembelajaran kontekstual dan aplikatif, seperti simulasi laporan keuangan. Meski berdampak positif, hambatan seperti keterbatasan bahan ajar dan kesiapan guru masih signifikan. Hambatan ini perlu diatasi dengan meningkatkan transformasi pendidikan akuntansi di SMK supaya lebih sesuai dengan kebutuhan dunia kerja. Kata Kunci: kesiapan guru; Kurikulum Merdeka; pendidikan akuntansi; pembelajaran berbasis proyek; sumber daya pendidikan